Mini Invelox Wind Harvesting System with IoT Monitoring (MIWHS-IoT) - Mohamad Isa, Mohamad Nabil Amiruddin; Ubin, Aizan (Evolution in Electrical and Electronic Engineering, 2023)
The mini Invelox wind harvesting with IoT monitoring (MIWHS-IoT) project aims to demonstrate the feasibility of using an Invelox system, a wind turbine that uses a series of funnels and ducts to increase wind speed, in combination with a boost converter circuit and IoT monitoring to improve the performance and efficiency of the system. The project includes the design and implementation of an Invelox system prototype, as well as the integration of sensors for monitoring wind speed and output voltage, and a boost converter circuit to step up the voltage. The sensor data is transmitted to a cloud-based platform for analysis and visualization using Blynk, an IoT platform for building IoT applications. The results of the project show that the Invelox system can generate a significant increase in output voltage and the IoT monitoring system provided valuable insights into the performance and efficiency of the system, and support for optimizing the system operation. The project provides a proof-of-concept for using an Invelox system in a small-scale wind harvesting application and can be used as a basis for further research and development in this field.